Harmonics detection via input observer with grid frequency fluctuation. (February 2020) - Li, Po; Jin, Wentao; Li, Ruiyu; Guan, Mingjie
Highlights: A real-time harmonics detection method based on input observer is proposed. Solving the problem of harmonics detection error caused by frequency fluctuation. This method shall not be affected by the circuit topology. Abstract: In this paper, a real-time detection method based on input observer is introduced for harmonics extraction of the grid currents in the case of fundamental frequency fluctuation. The proposed method has the advantages of fast detection speed and high detection precision, and can deal with the sudden changes in grid currents amplitudes and fundamental frequency. It works as follows: first of all, a phase-locked loop is used to extract the phase of grid currents in real-time. Then a state space model is constructed with grid currents and the harmonic components as unknown state variables. Finally, with the detected real-time phase, a linear time-varying observer based on the state space model is designed to estimate the unknown state variables. Its stability is guaranteed by Lyapunov function and LaSalle's Invariance Principle. Thus the extraction of grid currents harmonics is realized. Both simulation and experimental results show that the harmonic components of grid currents can be quickly and accurately extracted by proposed method even if the grid currents are distorted.